High‐resolution diffusion tensor imaging identifies hippocampal volume loss without diffusion changes in individuals with prenatal alcohol exposure. (26th May 2022) - Solar, Kevin Grant; Treit, Sarah; Beaulieu, Christian
Abstract: Background: Magnetic resonance imaging (MRI) studies of prenatal alcohol exposure (PAE) commonly report reduced hippocampal volumes, which animal models suggest may result from microstructural changes that include cell loss and altered myelination. Diffusion tensor imaging (DTI) is sensitive to microstructural changes but has not yet been used to study the hippocampus in PAE. Methods: Thirty‐six healthy controls (19 females; 8 to 24 years) and 19 participants with PAE (8 females; 8 to 23 years) underwent high‐resolution (1 mm isotropic) DTI, anatomical T1‐weighted imaging, and cognitive testing. Whole‐hippocampus, head, body, and tail subregions were manually segmented to yield DTI metrics (mean, axial, and radial diffusivities—MD, AD, and RD; fractional anisotropy—FA), volumes, and qualitative assessments of hippocampal morphology and digitations. Automated segmentation of T1‐weighted images was used to corroborate manual whole‐hippocampus volumes. Results: Gross morphology and digitation counts were similar in both groups. Whole‐hippocampus volumes were 18% smaller in the PAE than the control group on manually traced diffusion images, but automated T1‐weighted image segmentations were not significantly different. Subregion segmentation on DTI revealed reduced volumes of the body and tail, but not the head. There were no significant differences in diffusion metrics between groups for any hippocampal region. Correlations between age and volume were not significant in either group, whereas negative correlations between age and whole‐hippocampus MD/AD/RD, and head/body (but not tail) MD/AD/RD were significant in both groups. There were no significant effects of sex, group by age, or group by sex for any hippocampal metric. In controls, seven positive linear correlations were found between hippocampal volume and cognition; five of these were left lateralized and included episodic and working memory, and two were right lateralized and included working memory and processing speed. In PAE, left tail MD positively correlated with executive functioning, and right head MD negatively correlated with episodic memory. Conclusions: Reductions of hippocampal volumes and altered relationships with memory suggest disrupted hippocampal development in PAE. Abstract : High‐resolution diffusion tensor imaging (DTI) demonstrated reduced whole‐hippocampus volume and no differences in hippocampal DTI metrics, indicating preserved microstructure in prenatal alcohol exposure (PAE). Age‐related changes over 8‐24 years were found for hippocampal diffusivities, but not volume, in PAE and controls. Correlations between larger hippocampal volumes and cognitive scores were only found in controls, and correlations between mean diffusivity and cognitive scores were found only in PAE, suggesting that PAE may alter the relationship between hippocampal structure and memory performance.